Distribuição de renda, subdesenvolvimento e a relação centro-periferia - Jorge Luis Teixeira Avila (2011)
The issue of income distribution has always been addressed by the mainstream literature as a result of economic development, not as one of its determinants. However, since the 1990s, theoretical contributions that consider income concentration as an obstacle to development have become widespread in the literature. Although most recent empirical studies indicate a negative causality between inequality and economic development, there is no consensus about the importance of the different transmission channels. This dissertation addresses this issue in an alternative manner and, to some extent, indirectly by approaching the relationship between income concentration and pattern of international trade specialization. The results obtained in this study show an adverse effect of inequality on a countrys pattern of trade specialization in terms of technological content and sophistication level of exported goods. The relationship was significant in both empirical strategies adopted. For the technological content of exports, the empirical analysis showed a negative effect of inequality on exports in low, medium and high technology industries, while this effect was positive for primary products and natural resource based industries. Regarding the sophistication of exports, the results indicated that, controlling for other determinants, such as per capita income, inequality negatively affects the degree of sophistication of a countrys exports.